2001
DOI: 10.1177/088307380101600916
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Breath-Holding Spells Into Late Childhood

Abstract: Breath-holding spells commonly occur during infancy. The disorder represents a self-limited, benign phenomenon, and breathholding spells almost always resolve by school age. Their continuing occurrence beyond this age is exceedingly uncommon and may create diagnostic confusion. We recently encountered an 8-year-old boy who continues to experience breath-holding spells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 6 publications
3
11
0
Order By: Relevance
“…We believe that in children with breath-holding spells, these control mechanisms are likely immature and hence easily dysregulated by triggers resulting in prolonged expiratory apnea and inhibition of inspiration. 11 Inability to breathe in (mislabeled as breath-holding) experienced by our child and also previously reported 13 at the onset of spell indicates the failure of the inspiration-expiration switch of the central respiratory control mechanisms in the genesis of cyanotic breathholding spells. Theophylline through its various positive respirogenic effects is able to set the central respiratory neural drive in an ''overdrive'' mode, rendering it resistant to dysregulation by triggers.…”
Section: Discussionsupporting
confidence: 68%
“…We believe that in children with breath-holding spells, these control mechanisms are likely immature and hence easily dysregulated by triggers resulting in prolonged expiratory apnea and inhibition of inspiration. 11 Inability to breathe in (mislabeled as breath-holding) experienced by our child and also previously reported 13 at the onset of spell indicates the failure of the inspiration-expiration switch of the central respiratory control mechanisms in the genesis of cyanotic breathholding spells. Theophylline through its various positive respirogenic effects is able to set the central respiratory neural drive in an ''overdrive'' mode, rendering it resistant to dysregulation by triggers.…”
Section: Discussionsupporting
confidence: 68%
“…Breath holding spells were observed more frequently in boys than in girls. In our study the ratios were found to be 1.1: 1, 3: 1, 1.7:1 and 1.3: 1 in Ashrafi et al, 15 Lombroso et al, 5 Diamario et al 8 and Goraya et al 16 studies respectively. In a group of 384 children (3 months to 4 years) studied by Livingston, the mean age at onset of Breath holding spell was 12 months.…”
Section: Resultssupporting
confidence: 54%
“…In Ashrafi et al’s study ( 7 ), anger and pain were the common triggering factors (65.1%). Other studies reported that BHS was provoked by frustration, anger, fear, or pain, i.e., Goraya et al ( 17 ), Daoud et al ( 18 ), and Evans Owen ( 19 ). Consanguinity was present in 53.13% of patients, and these results were much higher than those of Ashrafi et al’s study ( 7 ) (30%) or Hilal Mocan et al’s study ( 20 ) (8.7%).…”
Section: Discussionmentioning
confidence: 99%